Implementasi Kebijakan Peraturan Daerah Nomor 8 Tahun 2012 tentang Retribusi Izin Gangguan dan Kontribusinya terhadap Peningkatan Pendapatan Asli Daerah (PAD) Kota Pekanbaru Tahun 2012-2014 - Sofyan Hadi; Ishak (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
In the Pekanbaru City Regional Regulation No. 8 of 2012 concerning Disturbance Permits in Article 3 has been explained that this permit is valid for five (5) years and shall re-register every year by paying a levy. But in reality there are many employers who do not pay the levy each year, mainly in the district Charming. The approach used in this study is qualitative and classify informant research include key informants, key informants and informant extra. Data collection techniques used in the form of in-depth interviews and secondary data analysis with qualitative analysis techniques procedure; reduction, data presentation and verification / conclusions. The results showed that the retribution permit interference in Pekanbaru has decreased, even though efforts are minor nuisance levels continue developing States at any time for the purpose of investment employers by various businesses. Resistor in retribution disorder is an enumeration of objects levy is less good, less than the maximum dissemination and awareness of the poor to pay the levy.